2007
DOI: 10.1021/jf0626819
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of trans-Caftaric Acid Administered into the Rat Stomach

Abstract: trans-Caftaric acid is the most abundant nonflavonoid phenolic compound in grapes and wines. It occurs in chicory and is one of the bioactive components of Echinacea purpurea. In order to fill the gap of knowledge about its bioavailability in mammals, we investigated its absorption, tissue distribution, and metabolism in rats. Assuming that the stomach is a relevant site of absorption of dietary polyphenols, a solution of trans-caftaric acid was maintained in the ligated stomach of anaesthetized rats for 20 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…Caftaric and fertaric acids exist in their trans form, mainly localized in the grape pulp and, during the grape pressing, being quickly released into the juice, while a negligible fraction of the cis isomer has been found for p-coutaric acid. Contrary to this, the trans and cis isomers of p-coutaric acid are less extractable since they are mostly localized in the grape skin, being partially responsible for the astringent properties of both grapes and wines [14]. Although the white wines have a lower concentration of phenolic compounds compared to the red ones, they contain, in turn, a high quantity of caftaric acid.…”
Section: Phenolic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caftaric and fertaric acids exist in their trans form, mainly localized in the grape pulp and, during the grape pressing, being quickly released into the juice, while a negligible fraction of the cis isomer has been found for p-coutaric acid. Contrary to this, the trans and cis isomers of p-coutaric acid are less extractable since they are mostly localized in the grape skin, being partially responsible for the astringent properties of both grapes and wines [14]. Although the white wines have a lower concentration of phenolic compounds compared to the red ones, they contain, in turn, a high quantity of caftaric acid.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Although the white wines have a lower concentration of phenolic compounds compared to the red ones, they contain, in turn, a high quantity of caftaric acid. Hydroxycinnamic acids and their tartaric esters constitute the main class of nonflavonoid phenolics in red wines and the main class of phenolic compounds in white wines [14]. During the fermentation process, these esters are partially hydrolyzed, resulting free hydroxycinnamic acids, transformed then into ethyl coumarate and ethyl caffeate [15].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…1), ester of caffeic acid and tartaric acid, only absorption from the stomach and microbial metabolism were studied. It appeared that it was absorbed from the stomach, and was found under its intact form and under transfertaric acid form in the plasma, excreted in urine only under trans-fertaric acid form (Vanzo et al 2007). Incubation with active faecal flora showed that in the caecum, caftaric acid could be metabolized in two main metabolites, 3-hydroxyphenylpropionic and benzoic acids (Gonthier et al 2006).…”
Section: Hydroxycinnamic Acid Bioavailabilitymentioning
confidence: 99%
“…Pharmacokinetic studies demonstrate that natural or synthesized caffeic acid derivatives (e.g. caftaric acid, chlorogenic acid and echinacoside) are quickly absorbed in the rat stomach, but rapidly eliminated from circulation (Jia et al, 2006; Lafay et al, 2006; Vanzo et al, 2007). Matthias et al (2004) suggests a low bioavailability for caffeic acid derivatives of Echinacea based on their poor permeability through Caco-2 monolayers, a model for the intestinal epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%